2011
DOI: 10.1109/tuffc.2011.2122
|View full text |Cite
|
Sign up to set email alerts
|

Frequency shifts in plate crystal resonators induced by electric, magnetic, or mechanical fields in surface films

Abstract: We study frequency shifts in plate crystal resonators with surface films. The films are multiphysical, including the effects of inertia, stiffness, intrinsic stress, piezoelectric coupling, and piezomagnetic coupling. Mindlin's two-dimensional equations for a crystal plate with two elastic surface films are generalized to include the multiphysical effects of the films. They are used to study thickness-shear vibrations of a rotated Y-cut quartz plate with initial fields resulting from the mechanical, electric, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…He revealed that the e ect of piezoelectricity on force-frequency coe cient of incomplete quartz resonating disk is about 7 percent when the force azimuth angle is zero [17]. In addition to Mindlin procedure, other analytical methods like perturbation method, developed by Tiersten [18], and full numerical methods are used to determine frequency shift in quartz resonators due to external perturbations [14,[19][20][21][22][23]. The accuracy of these methods is acceptable, but they are complicated and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…He revealed that the e ect of piezoelectricity on force-frequency coe cient of incomplete quartz resonating disk is about 7 percent when the force azimuth angle is zero [17]. In addition to Mindlin procedure, other analytical methods like perturbation method, developed by Tiersten [18], and full numerical methods are used to determine frequency shift in quartz resonators due to external perturbations [14,[19][20][21][22][23]. The accuracy of these methods is acceptable, but they are complicated and time consuming.…”
Section: Introductionmentioning
confidence: 99%